JOS: INITIATION OF EMPLOYEE JOB SATISFACTION IMPROVEMENT MODEL IN TERMS OF ETHICS AND WORK STRESS - Lestari, Selvia Puji; Putra , Febrianur Ibnu Fitroh Sukono; Arsanda , Tiara Daffa (Lembaga Pengembangan Kinerja Dosen, 2021)
This study aims to determine and analyze the effect of work ethics on employee job satisfaction, the effect of job stress on employee job satisfaction, and the effect of work ethics and work stress on employee job satisfaction at PT. PLN (Persero) UIP3BS UPT Medan. The population in this study were all employees of PT. PLN (Persero) UIP3BS UPT Medan, totaling 60 people. The sampling technique used is a saturated sample; thus, the sample in this study was 60 employees of PT. PLN (Persero) UIP3BS UPT Medan. The data collection technique used is a questionnaire. The data analysis technique used is multiple regression. The results showed a positive and significant effect of work ethics on job satisfaction, there was a negative and significant effect of job stress on job satisfaction, and there was an influence of work ethics and work stress on job satisfaction at PT. PLN (Persero) UIP3BS UPT Medan